Os saberes da linguística e o ensino de língua portuguesa, a relação oficial - Herrmann, Gabriela Persio (2013)
In search of answers about the constitution of Portuguese language teaching, we analyzed in our study three official documents that regulate the curriculum of subject, namely: Curriculum Guides for teaching 1st grade - Portuguese (1975 - SP); Curriculum Proposal for Portuguese Language teaching - 1st grade (1988 - SP) and Lessons of Rio Grande (2009 - RS). Our main aim was to observe how is established the relation between Portuguese language teaching and knowledge of linguistics, in an official context. Thereunto, we construct our interpretation through close reading of documents in general, looking for concepts of language, grammar, LP teaching, and the concept of language. Through a socio-historical view in light of dialogic assumptions of Bakhtin Circle, we built our opposition to official documents, understood as historically situated utterances, which carry information about LP teaching and even the intentions of its producers towards privileged readers, the teachers. These concepts might reveal that the renovation of the LP teaching was formed, both in 1970, in 1980, as in 2000 on denial of traditional practices, based primarily on the teaching of traditional grammar. This opposition was taken discursively through several resources, revealing in all these materials, in one way or another, that the relation between linguistics and education would be the solution to renew LP teaching.We believe that the relation between knowledge of linguistics and LP teaching, demarcated in official documents, as Bunzen (2011) argues, is a facet of the history of LP subject that one which there was an emergency to bring studies the science of language to classroom.